Analyses of a high pressure ratio intercooled direct Brayton helium gas turbine cycle for Generation IV reactor power plants - Gad-Briggs, Arnold; Pilidis, Pericles; Nikolaidis, Theoklis (ASME, 2016)
The intercooled cycle (IC) as an alternative to the simple cycle recuperated (SCR) and intercooled cycle recuperated (ICR) is yet to be fully analyzed for the purpose of assessing its viability for utilization within Generation IV nuclear power plants (NPPs). Although the benefits are not explicitly obvious, it offers the advantage of a very high overall pressure ratio (OPR) in the absence of a recuperator. Thus, the main objective of this study is to analyze various pressure ratio configurations, the effects of varying pressure ratio including sensitivity analyses of component efficiencies, ambient temperature, component losses and pressure losses on cycle efficiency, and specific work of the IC, including comparison with the SCR and ICR. Results of comparison between the IC and the SCR and ICR derived that the cycle efficiencies are greater than the IC by ∼4%∼4% (SCR) and ∼6%∼6% (ICR), respectively. However, the pressure losses for IC are lower when compared with the SCR and ICR. Nonetheless, heat from the turbine exit temperature of the IC can be used in a processing plant including the possibility of higher turbine entry temperatures (TETs) to significantly increase the cycle efficiency in a bid to justify the business case. The analyses intend to bring to attention an alternative to current cycle configurations for the gas-cooled fast reactors (GFRs) and very-high-temperature reactors (VHTRs), where helium is the coolant. The findings are summarized by evaluating the chosen pressure ratio configurations against critical parameters and detailed comparison with the SCR and ICR.
Keywords: Gen IV; efficiency; specific work; cycle; nuclear power plants; performance; split; intercooled